تقدير تكلفة راس المال للقطاعات المدرجة في سوق المال السعودي - بوحفص، مول الضاية; مسعودي، علي (جامعة الوادي University of Eloued, 2024)
This study aims to explore the key models proposed for measuring the cost of capital, with a focus on the Capital Asset Pricing Model (CAPM) and its assumptions, particularly the heterosced as ticity hypothesis. The study also seeks to discuss the applicability of the CAPM in emerging markets, especially in Arab financial markets such as the Saudi financial market. The study concluded that the heterosced as ticity hypothesis in the Capital Asset Pricing Model is not valid in the Saudi financial market, particularly as mostdecision-makers use itextensively, leading to potentially in accuratefinancial decisions
Estimating the cost of capital for sectors listed on the Saudi Stock Market
Keywords: تكلفة راس المال; عائد; مخاطرة; نموذج تسعير أصول رأسمالية; Cost of capital; Return; Risk; Capital Asset Pricing Model; Financial market.